The Modern Doctrinal Definition of Militant Democracy - Yaremenko, Mykhailo (Problems of legality, 2026)
The beginning of the largest war in Europe since World War II forces Ukraine to use the concept of militant democracy more actively. At the same time, the question arises of what exactly militant democracy is now and how our foreign colleagues interpret it in the 21st century. In fact, according to modern scholars, the need for militant democracy appeared again – it is as relevant now as it was at the time of its creation. However, even despite such a need for its moderate application, it should be recognized that militant democracy has changed over time and can no longer be identical to how it was perceived in the middle of the 20th century. The purpose of the article is to comprehensively reveal the concept of militant democracy from the modern perception. Achieving the outlined goal was made possible through the use of a complex of methods of scientific knowledge, in particular, content analysis (for comprehensive knowledge of scientific works of scientists of the early 21st century), the formal-logical method (to identify certain patterns, stable structures, relationships, and inconsistencies in scientific works), the comparative-legal method (by studying the experience of other countries and the positions of various scientists, to provide a comprehensive understanding that would allow the application of the works cited in the article). In the face of new challenges that force us to turn to the mechanisms offered by militant democracy, it is worth updating our vision and approach to understanding this concept, having received a comprehensive vision from foreign lawyers and scientists.